2021
DOI: 10.1155/2021/5535562
|View full text |Cite
|
Sign up to set email alerts
|

β‐Sitosterol Alters the Inflammatory Response in CLP Rat Model of Sepsis by Modulation of NFκB Signaling

Abstract: Purpose. Sepsis originates from the host inflammatory response, especially to bacterial infections, and is considered one of the main causes of death in intensive care units. Various agents have been developed to inhibit mediators of the inflammatory response; one prospective agent is β-sitosterol (βS), a phytosterol with a structure similar to cholesterol. This study is aimed at evaluating the effects of βS on the biomarkers of inflammation and liver function in cecal ligation and puncture- (CLP-) induced sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Besides CS, DG, and HH, beta-sitosterol was also found to exist in Hechtia glomerata Zucc., which was used as a source in ethnomedicine to treat various diseases derived from bacterial infections, such as sepsis, bronchitis, and laryngitis ( Stefani et al, 2019 ). Beta-sitosterol was predicted to mediate NF-κB signaling pathway ( Kasirzadeh et al, 2021 ) and was found to significantly reduce the pro-inflammatory cytokines in the sera of cecal ligation and puncture-induced septic rats, such as TNF-α and NF-κB mRNA expressions. In addition, stigmasterol was proved to decrease the levels of cyclooxygenase-2 (Cox-2) and NF-κB (p65) in the brain of rats, thereby attenuating inflammation and improving antioxidant defenses ( Liang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides CS, DG, and HH, beta-sitosterol was also found to exist in Hechtia glomerata Zucc., which was used as a source in ethnomedicine to treat various diseases derived from bacterial infections, such as sepsis, bronchitis, and laryngitis ( Stefani et al, 2019 ). Beta-sitosterol was predicted to mediate NF-κB signaling pathway ( Kasirzadeh et al, 2021 ) and was found to significantly reduce the pro-inflammatory cytokines in the sera of cecal ligation and puncture-induced septic rats, such as TNF-α and NF-κB mRNA expressions. In addition, stigmasterol was proved to decrease the levels of cyclooxygenase-2 (Cox-2) and NF-κB (p65) in the brain of rats, thereby attenuating inflammation and improving antioxidant defenses ( Liang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The level of TNF-α was reported to be increased significantly in LPS-stimulated BMDMs ( Liu et al, 2020 ). Comparatively, TNF-α could be reduced by baicalin (MOL002776) in the blood of sepsis mice ( Chen et al, 2016 ) and was reduced by beta-sitosterol [MOL000358 (CS, DG, and HH)] ( Kasirzadeh et al, 2021 ), caffeic acid [MOL000223 (CX, DS, and HH)] ( Chen et al, 2019 ). A Chinese formula, RDN, had been proved to ameliorate LPS-induced acute lung injury by downregulating TNF-α ( Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, Lee et al found that Candida albicans -infected mice treated with plant-derived β-sitosterol glucosides (daucosterol) survived longer than untreated mice and had greater numbers of activated splenic lymphocytes compared to untreated mice 38 . β-sitosterol glucosides may also play a protective role in the septic process by mitigating inflammation in a rat model of sepsis 39 . Lastly, the effect of β-sitosterol glucosides on the immune response was also observed in a human study 40 .…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6-Trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice could be suppressed by SITO through downregulating the expression of NF-κB-modulated proinflammatory cytokines, including TNF-α, IL-1β, and IL-6 [11]. It could also alleviate the sepsis process by inhibiting the NF-κB signaling pathway in a cecal ligation and puncture (CLP)-induced septic rat model [12]. SITO has also been shown to mitigate the proinflammatory responses caused by influenza A by inhibiting both RIG-1 and STAT1 pathways other than the NF-κB signaling pathway [13].…”
Section: Introductionmentioning
confidence: 99%